2022
DOI: 10.1038/s41533-022-00269-9
|View full text |Cite|
|
Sign up to set email alerts
|

Care-seeking and delay of care during COPD exacerbations

Abstract: Patients who receive earlier treatment for acute exacerbations of chronic obstructive pulmonary disease (COPD) have a better prognosis, including earlier symptom resolution and reduced risk of future emergency-department visits (ED) or hospitalizations. However, many patients delay seeking care or do not report worsening symptoms to their healthcare provider. In this study, we aimed to understand how patients perceived their breathing symptoms and identify factors that led to seeking or delaying care for an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Delays in seeking medical care may be multifactorial. Previous studies have demonstrated that delay may occur due to resource availability (including transportation, finances or insurance, homelessness), subjective interpretation of symptoms (minimal versus severe), fear of medical care, fear of infection, fear of overcrowded hospitals, or financial concerns [12][13][14][15][16][17]. The National Healthcare for the Homeless Council in 2019 stated that homeless patients have higher rates of illness and die 12 years earlier than the general population in the United States [18].…”
Section: Table 2: Reasons For Delay In Diagnosis Of Intracranial Trau...mentioning
confidence: 99%
“…Delays in seeking medical care may be multifactorial. Previous studies have demonstrated that delay may occur due to resource availability (including transportation, finances or insurance, homelessness), subjective interpretation of symptoms (minimal versus severe), fear of medical care, fear of infection, fear of overcrowded hospitals, or financial concerns [12][13][14][15][16][17]. The National Healthcare for the Homeless Council in 2019 stated that homeless patients have higher rates of illness and die 12 years earlier than the general population in the United States [18].…”
Section: Table 2: Reasons For Delay In Diagnosis Of Intracranial Trau...mentioning
confidence: 99%
“…Experience shows that patients are often slow or loathe to self-report symptoms that indicate an emerging AECOPD. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…Experience shows that patients are often slow or loathe to self-report symptoms that indicate an emerging AECOPD. 12,13 To pre-identify exacerbations, physiologic and spirometric measures have been used including changes in pulse rate, peripheral oxygen saturation, blood pressure, body temperature, forced expiratory volume in the first second (FEV1), and respiratory rate. 14 However, devices currently available and commonly used by COPD patients, such as spirometers and pulse oximeters, may be inadequate to accurately pre-identify AECOPDs.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Delays in diagnosis and inconsistent delivery of optimized guideline-based COPD care contribute to adverse outcomes. 5 COPD is also a significant driver of UK healthcare expenditure with costs incurred primarily by hospital admissions. 6 The direct costs of managing COPD to the NHS are projected to increase substantially to £2.5bn per year by 2030 due to increases in incidences of COPD.…”
Section: Introductionmentioning
confidence: 99%